Peran Bank Indonesia dalam Menstabilkan Perekonomian dan Jumlah Uang Beredar Melalui Kebijakan Moneter - Yunan Hendra Permana; Nur'aeni Nur'aeni; Setiawan Setiawan (Ma'soem University, 2022)
Based on the observation, that the background in this research is the economic condition and the money supply in Indonesia as seen from the last five years, then what policies have been issued by Bank Indonesia.This study aims to determine the mechanism and role of Bank Indonesia in maintaining economic stability and the money supply through Monetary Policy.The object of research in this is located at the Representative Office of Bank Indonesia, West Java Province. The type of this research is descriptive qualitative with a qualitative approach. The source of the data obtained in the form of primary data with field observations and interviews, namely by direct observation in the field and a question and answer process with resource persons to exchange information and ideas in obtaining information and using secondary data by obtaining information through the official website of Bank Indonesia and the Central Statistics Agency. The results of this study indicate that the mechanisms and roles performed by Bank Indonesia in maintaining economic stability and the Money Supply through Monetary Policy are first, through the BI 7DRR (Bank Indonesia 7 Day Repo Rate) interest rate and Open Market Operations, Second, by using policy instruments. Macroprudential and Discount Policy.